Cover Feature: Intramolecular Proton and Charge Transfer of Pyrene‐based trans‐Stilbene Salicylic Acids Applied to Detection of Aggregated Proteins (ChemPhysChem 22/2018). Issue 22 (8th November 2018) - Zhang, Jun; Wang, Jun; Sandberg, Alexander; Wu, Xiongyu; Nyström, Sofie; LeVine, Harry; Konradsson, Peter; Hammarström, Per; Durbeej, Bo; Lindgren, Mikael
Abstract : The Cover Feature shows the structure of two analogous fluorescent amyloid fibril probes Py1SA and Py2SA based on a trans‐stilbene salicylic acid pyrene scaffold. Excited state proton transfer coupled‐charge transfer is more efficient in Py1SA compared to Py2SA rendering vastly different emission spectra from the molecules bound to amyloid fibrils depicted in the background. More information can be found in the Article by J. Zhang et al. onpage 3001 in Issue 22, 2018 (DOI:10.1002/cphc.201800823 ).